Adjunctive transcranial direct current stimulation for cognitive improvement in schizophrenia: insights from a systematic review and exploratory meta-analysis - Yao, Gaolei; Huang, Yuan; Ping, Junjiao; Han, Yixuan; Lu, Liming; Liu, Xinxia; Lu, Huipeng (Frontiers in Psychiatry, 2025)
IntroductionTo objectively and accurately evaluate the clinical efficacy of transcranial direct current stimulation (tDCS) for schizophrenia, we conducted this systematic review and exploratory meta-analysis (PROSPERO: CRD420251002632).MethodsFirstly, randomized controlled trials (RCTs) related to the adjunctive use of tDCS for schizophrenia were searched on PubMed, Embase and Web of Science databases according to search strategies developed in advance. Secondly, the eligible articles were screened according to the inclusion and exclusion criteria. Finally, the data were extracted and a complete meta-analysis was performed. Meanwhile, we also completed publication bias analysis and sensitivity analysis. Statistical analysis was conducted using RevMan software (version 5.4).ResultsWe ultimately included 11 eligible RCTs. The results of the exploratory meta-analysis indicated that the adjunctive use of tDCS seems to be able to enhance the cognitive function of patients (the Paced Auditory Serial Addition Task: standardized mean deviation (SMD) = 3.57, 95% confidence interval (CI) (2.60, 4.54), P < 0.00001). Subgroup analyses showed that the adjunctive use of tDCS at 15 sessions (Clinical Global Impression-Schizophrenia scale: SMD= -0.56, 95% CI (-0.87, -0.25), P=0.0004) or twice daily (Clinical Global Impression-Schizophrenia scale: SMD= -0.85, 95% CI (-1.67, -0.03), P=0.04) also decreased the disease severity.DiscussionThis exploratory meta-analysis revealed that tDCS in the treatment of schizophrenia appears capable of improving cognitive function and effectively reducing the severity of the disease. What’s more, tDCS has great development potential in schizophrenia, and it may be written into the guidelines for non-drug treatment of schizophrenia in the future. As a matter of fact, this exploratory study points out the direction for future scientific research and clinical practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251002632.